(untitled) (Revista Nacional de Administración, 2025)
Effective human capital management is hindered by factors such as poor leadership, lack of employee engagement, inadequate knowledge sharing, and talent wastage. Even educational institutions face challenges in attracting and retaining human capital. This study investigates the relationship between employee engagement and employee productivity in selected public and private universities in Ogun State, Nigeria. A survey research design was employed, with a sample size of 586 university employees selected from a population of 6,058 from 4 universities (Babcock University, Covenant University, Federal University of Agriculture, Abeokuta and Olabisi Onabanjo Universities located in Ogun State) using Cochran (1997) equation. A self-structured questionnaire was administered to the respondents, the research instrument was validated by the average variance (0.831). The questionnaire’s reliability was ensured with Cronbach’s Alpha coefficients ranging from 0.765 to 0.901 for the constructs, which suggests that the instrument used for evaluation is highly reliable and data gathered was analyzed using inferential statistics (Pearson correlation analysis). The result of the analysis showed there was a positive relationship between employee engagement and employee productivity in selected public and private universities in Ogun State (r= .386, p<0.05). The study concluded that employee engagement has positive effect on employee productivity. The study therefore recommended that universities must be consistent with employee engagement activities such as empowerment; promoting and encouraging teamwork; assisting employees to grow, develop and where appropriate providing support and recognition.